Renewable energy integration : practical management of variability, uncertainty and flexibility in power grids - Jones, Lawrence E. (Amsterdam : Elsevier, AP, 2014)
'Renewable Energy Integration is a ground-breaking new resource, the first to offer a distilled examination of the intricacies of integrating renewables into power grid and electricity markets. It offers informed perspectives from internationally renowned experts on the challenges to be met, and solutions based on demonstrated best practices developed by operators around the world. The book's focus on practical implementation of strategies provides real-world context for theoretical underpinnings and the development of supporting policy frameworks. The book considers a myriad of wind, solar, wave and tidal integration issues, thus ensuring that grid operators with low or high penetration of renewable generation can leverage the victories achieved by their peers. Renewable Energy Integration highlights, carefully explains, and illustrates the benefits of advanced technologies and systems for coping with variability, uncertainty, and flexibility'--
Includes bibliographical references and index.
Keywords: Renewable energy integration; Renewable energy sources; Smart power grids; Electric power distribution